Comment on Khan S P Khan, et al. (J Pak Med Assoc. 74: 1654-1658, September 2024) Role of Oral Hypoglycaemic Drugs in Preventing Complications in Non-Alcoholic Fatty Liver Disease with Type 2 Diabetes Mellitus - Anas Babar (Journal of the Pakistan Medical Association, 2025)
Dear Editor, I recently came across the paper "Role of OralHypoglycaemic Drugs in Preventing Complications inNon-Alcoholic Fatty Liver Disease with Type 2 DiabetesMellitus" in your esteemed journal. The study effectivelyhighlights the significance of empagliflozin andmetformin in reducing fatty liver changes and liverenzymes in NAFLD patients with type 2 diabetes mellitus.Current data strongly supports empagliflozin, an SGLT2inhibitor, in effectively managing blood glucose levels,reducing hepatic steatosis, and lowering cardiovascularrisk among these patients1.Nevertheless, the study’s restricted sample size and highpatient dropout rate curtail the broad applicability of thefindings. It would be advantageous to conduct larger,multicenter trials with extended follow-up periods tothoroughly investigate the sustained impact of thesedrugs on hepatic and metabolic outcomes. Such datawould substantially enhance clinical guidelines formanaging NAFLD in T2DM patients. Continued...